Rewrite the equation in standard form by expanding it.
y= 3 (x+2)^2 - 4
1 answer:
Answer:
y = 3x^2 + 12x + 8
Step-by-step explanation:
To rewrite in standard from by expanding the equation using the distributive property.
y= 3 (x+2)^2 - 4
y = 3(x^2 + 4x + 4) - 4
y = 3x^2 + 12x + 12 - 4
y = 3x^2 + 12x + 8
You might be interested in
Answer:
yes
Step-by-step explanation:
it just needs to have three sides
Answer:
nice work hope to see it once its finished!
Step-by-step explanation:
Answer:
A
Step-by-step explanation:
The ratio is
1 inch : 100 miles
0.5 inch : X miles
1/100 = 0.5/X
X = 0.5 ÷ 1/100
X = 0.5 × 100/1
X = 50
The answer is B. Would you like an explanation why?
Answer:
A
Step-by-step explanation: